Hubungan Minat Belajar Siswa dengan Prestasi Belajar Bahasa Jerman - Ilham Akbar; Misnah Mannahali (Universitas Negeri Makassar, 2023)
Abstract. This research is a correlation research to get the relationship between interest in learning and German learning success of students at SMA Negeri 11 Makassar. The variables of this research were the learning interests of the students (X) and their German learning success (Y). The population of this research consisted of all grade XII students, with a total class size of 4 grades and a total of 121 students. The research sample consists of 31 XII IPS 1 students who were randomly selected. The files for this research were obtained from a scaled interest in learningtest with documentation from student reports. Based on the results of the Product Moment Correlation data analysis, it turns out that r count (0.781) > r table (0.344) with a significant level at 0,05%. The result of the file analysis shows that there is a strong relationship between interest in learning and learning success at SMA Negeri 11 MakassarKeyword: Interest, Performance, Learning, German